Exigências nutricionais de cálcio e fósforo para mantença e ganho de peso de cordeiros Texel - Alves, Emanuelle Vargas (2017)
The goal of this paper was to estimate the calcium (Ca) and phosphorus (P) requirements of Texel lambs. 42 entire male lambs from Texel breed were used, weaned at 50 days of age, with an initial mean live weight (LW) of 21.2 kg, housed in individual stalls. Of the total, 6 were slaughtered after the 14-day adaptation period, while 24 animals were fed ad libitum and slaughtered at 25, 30, 35 or 40 kg LW. 12 animals were submitted to two levels of feed intake (70 or 55% of the intake ad libitum) and were slaughtered simultaneously with those lambs fed ad libitum and slaughtered at 40 kg LW. In the samples of the empty body composition, the phosphorus (P) contents were determined by spectrophotometer (colorimeter) and calcium (Ca) by atomic absorption spectrophotometry. The amount of mineral retained in the body was estimated as a function of the concentration of this nutrient in the samples. From these data, the regression equations for body composition were obtained. The maintenance requirement was calculated from the regression analysis between the minerals retained in the empty body of the animals submitted to the food restriction, as a function of the amount of each mineral consumed by the animals. The net requirements of macro minerals for LW gain were obtained by deriving the logarithmic allometric equation from the body's mineral content. Statistical analyzes were performed using SAS program (2014). The net requirements for maintenance in animals between 25 and 40 kg live weight were 1.1 g Ca/day and 0.52 g P/day and the net requirements per kg live weight gain for animals with 25 and 40 kg live weight were 7.98 and 7.30 g Ca and 3.06 and 2.96 g P, respectively. The requirements found are lower than those recommended by the international councils.